Selected determinants of the primary shools teachers lifestyle - Petr Jansa; Karel Kovář (Palacký University Olomouc, 2010)
The article targets the physical activities in the lifestyle of the primary schools teachers. This is a first and partial publication of the results of the questionnaire survey when 750 teachers of these schools were interviewed with a return of 612 questionnaires, i.e. 81,6 %, covering all the republic. The teachers sampling was diﬀerentiated into three categories: 23-35 years, 35-45 years, 45 + years, with a detailed description indicated in text. It comes through that teachers of our sampling are aware of the relevance of the sport and physical activities (91 % of the total) with a 7 % diﬀerence on behalf of women. The article mentions also the determinants impeding these activities, e.g. obesity, smoking and alcohol. The results are pointing to the very promising evaluation of the primary schools teachers from the point of view of the active lifestyle. The research survey is a part of research programmes indicated under MSM No. 0021620864, which will continue by locating the same determinants at secondary schools.